Adequate fruit and vegetable consumption and its association with overnutrition among primary school-aged children - Dian Luthfiana Sufyan; Utami Wahyuningsih (AcTion: Aceh Nutrition Journal, 2023)
Overnutrition among school-aged children increases substantially over the last decade. Among the direct causes of overweight/obesity is inadequate intake of fruit and vegetable. Prior studies have shown that fruit and vegetable (FV) is not merely the main source of vitamins andminerals, but also playing role on preventing weight gain through satiety regulation. This study aims to determine the association of FV consumption adequacy among 5-12 years schoolers and their overnutrition status. This cross-sectional study was conducted in Jakarta and Depok, carried out on 57 children who filled out an online questionnaire survey. Respondents’ characteristics were obtained through the self-administered online questionnaire. BMI for age z-score (BAZ) was calculated from the self-reported recall of body weight and height. The FV consumption was evaluated using the WHO STEP-wise questionnaire. Respondent’s characteristics were presented in frequency and percentage, while association test was done using Fisher Exact test (CI 95%). In this study, 40,4% of children were overweight and most children did not consume adequate portions of fruit and vegetable (73,7% and 57,9%, respectively). There are no significant association between FV consumption and children’s overnutrition (p= 0,171 and p= 0,788, respectively; CI 95%). Overall, a high proportion of children overnutrition was observed. However, there is no significant association was found between fruit and vegetable consumption and children’s overnutrition. There is a need for specific regulations and practices that may engage children in consuming fruit and vegetable on the daily basis.